2011
DOI: 10.1007/s10661-011-2381-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine in the rocks and sediments of volcanic areas in central Italy: total content, enrichment and leaching processes and a hypothesis on the vulnerability of the related aquifers

Abstract: Rock, sediment and water samples from areas characterised by hydrothermal alterations in the Sabatini and Vico Volcanic Districts, near Rome and the large city of Viterbo, respectively, were collected and analysed to determine the total fluorine (F) content and to understand the F geochemical background level in the volcanic districts of central Italy. Leaching and alteration processes controlling the high concentration of F in water were also investigated. Fluorine concentrations were directly determined (pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The hydrogeological circulation is complex due to the overlapping series of pyroclastic, lavas, and sedimentary units with different thickness and geometry. In addition, the regional fractures may play a role in producing hot spots of fluoride or arsenic concentration in groundwater in this area, as suggested by De Rita et al (2012) and Cinti et al (2015). All the above-mentioned geological factors contribute to the explanation of the high spatial variability of the concentration of the elements such as arsenic and fluoride and should be taken into account.…”
Section: Study Area Descriptionmentioning
confidence: 84%
“…The hydrogeological circulation is complex due to the overlapping series of pyroclastic, lavas, and sedimentary units with different thickness and geometry. In addition, the regional fractures may play a role in producing hot spots of fluoride or arsenic concentration in groundwater in this area, as suggested by De Rita et al (2012) and Cinti et al (2015). All the above-mentioned geological factors contribute to the explanation of the high spatial variability of the concentration of the elements such as arsenic and fluoride and should be taken into account.…”
Section: Study Area Descriptionmentioning
confidence: 84%
“…High F À concentrations in groundwater are generally related to natural sources, whereas only occasionally is of anthropogenic origin (Ozsvath, 2009;WHO, 2011). The occurrence of F À in volcanic-hydrothermal fluids is related to i) release of magmatic fluorine as HF through volcanic degassing, ii) upwelling of geothermal fluids and iii) water-rock interaction processes involving F-rich minerals (e.g., D'Alessandro, 2006;Sawyer and Opperheimer, 2006;Ozsvath, 2009;De Rita et al, 2011). High fluorine contents are generally found in volcanic rocks and hydrothermal deposits commonly associated with fluorite (CaF 2 ), fluorapatite (Ca 5 (PO 4 ) 3 F) and F-rich micas and/or amphiboles (where F À largely replaces OH À within the mineral structures).…”
Section: Fluoridementioning
confidence: 99%
“…The concentrations of fluorine tend to decrease with distance from hydrothermal alteration areas. Sedimentary deposits are usually characterized by low contents (De Rita et al, 2011). Radiometric characterization of volcanic and sedimentary rocks from SVD and VCVD (Trevisi et al, 2005) showed that the mean content of Rn-generating radionuclides 238 U and 226 Ra of tuffs (160 and 147 Bq/kg, respectively) and lavas (134 and 124 Bq/kg, respectively) from the Roman Magmatic Province is significantly higher than that of sedimentary formations (up to 49 and 24 Bq/kg, respectively) (Locardi and Mittempergher, 1971;Voltaggio et al, 2001).…”
Section: Geodynamic Evolution Hydrological and Petrological Settingsmentioning
confidence: 99%
See 2 more Smart Citations